Acenaphthylene‐Fused Cyclo[8]pyrroles with Intense Near‐IR‐Region Absorption Bands. Issue 41 (26th August 2013) - Okujima, Tetsuo; Ando, Chie; Mack, John; Mori, Shigeki; Hisaki, Ichiro; Nakae, Takahiro; Yamada, Hiroko; Ohara, Keishi; Kobayashi, Nagao; Uno, Hidemitsu
Abstract An acenaphthylene‐fused cyclo[8]pyrrole was synthesized by using an oxidative coupling reaction of the corresponding 2, 2′‐bipyrrole. Two conformational isomers 1 a and 1 b were isolated, and their molecular structures were elucidated by X‐ray crystallographic studies. The less‐polar and lower‐symmetry 1 b isomer can be converted into the 1 a isomer through a thermal ring flip. Application of the perimeter model developed by Michl to magnetic circular dichroism spectroscopic data and theoretical calculations demonstrate that there is a marked redshift of the near‐IR absorption maxima relative to cyclo[8]isoindole because there is a significant stabilization of the LUMO due to the differing effects of a fused ring expansion with acenaphthylene and benzene moieties on the frontier π molecular orbitals.